Peningkatan Kompetensi Siswa SMK sederajat Melalui Pelatihan Customer Service KSPPS di Kota Bandung Berbasis Maqashid Syariah - Ira Siti Rohmah Maulida; Arif Rijal Anshori; Neng Dewi Himayasari; Liza Dzulhijjah (Jurnal Ilmiah Ekonomi Islam, 2022)
The problems in vocational students for Islamic economic development today are students' knowledge and skills in understanding several Sharia contracts/transactions are in accordance with Islamic law. The subjects at the Islamic Banking Vocational School do not have a lot of Islamic economic law content in them. The solutions offered to deal with the problem of limited knowledge and skills of Islamic Economics Vocational School students are (1) providing training on the orientation / introduction of Sharia contracts for financing and funding transactions in accordance with Maqashid Syari'ah; (2) provide training or orientation on cooperatives and (3) provide training on how to deal with funding and financing customers. Activities to be carried out include 1) conducting pre-tests, to measure the level of student competence before training, (2) providing competency-based training on sharia transaction contracts, (3) providing training related to the concept of KSPPS financial institutions, (4) conducting post-tests. to measure the achievements achieved by students after training. And (5) provide recommendations to be able to take part in the competency test at the Professional Certification Institute.